Capital ideas: Modelling and measuring factors in the knowledge capital model - Ronald B. Davies; James R. Markusen (University College Dublin, UCD School of Economics, 2024)
One of the main challenges when analyzing multinational firms (MNEs) is that this group is comprised of a rich variety of firms engaged in a spectrum of activity. In response to the separate models describing one type of MNE or another, the Knowledge Capital model was developed in order to provide a unified framework. Although this did yield many empirically supported insights, it nonetheless had difficulty explaining to co-existence of FDI and trade among similar countries, a particular issue given that most FDI and trade takes place between such nations. While this can be resolved by adding in additional factor - capital - this raises several questions on how best to match the expanded theory to the data. In this paper, we provide an overview of the development of this literature, illustrate some of the difficulties in mapping the models to data, and provide several suggestions for future research including a need to model capital markets and taxation.
Keywords: F23; F12; 330; Knowledge Capital Model; Capital Measurement; Foreign Direct Investment; Multinational Firms